(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
An analysis of the results of the use of types and methods of corona discharge processing in electric technology using steaming (boiling), thermal neutralization, drying, and heat to reduce production costs and reduce moisture content for the development of techniques and technologies for the initial processing of cotton raw materials is presented. The main goal is to reduce the moisture content of the produced product to the optimal moisture content required for storage; that is, after reducing the moisture content of the product, it should be below the critical moisture content, and regardless of which oilseed is dried, the main task is to reduce the moisture content of the product to the required amount and, at the same time, increase the energy efficiency is not to lose its quality.